Factors shaping young tourists ' intentions to travel to Greece, Israel and Portugal: universal or idiosyncratic perceptions of young Greeks, Israelis and Portuguese? - S.h. Shahrabani; F. voulgaris; H. Desivilya-syna; E. Tsoukatos; V. Ambrósio; Loureiro, S. M. C. (Conference book proceedings of 9th Euromed conference of the Euromed academy of business research- innovation, entrepreneurship and Digital Ecosystems, 2016)
Tourism constitutes an important branch of economy, especially in countries experiencing economic crisis and harsh socio-political events. The current study compares the intention of young people from three different countries – Greece, Israel and Portugal - to travel to two selected destinations. For each country of origin the other two countries were the destination of interest. This research examined the factors affecting young tourists' intention to travel to different destinations assuming that those determinants depend on the country of origin as well as on the destination country.